The Relationship Of Workload To Employee Stress Levels In PT. Wahyu Pradana Binamulia Makassar: Workload To Employee Stress - Kristia Novia; Asrijal Bakri; Euis Dedeh Komariah; Rosmina Situngkir (STIKes Mandala Waluya Kendari, 2023)
Background: Each job has a different level of difficulty, depending on how heavy the workload is. If a person is given a light workload, then it is not a problem because it can be solved easily, but it is different if the work is considered a heavy workload, of course it has its own impact on each individual from fatigue to the onset of stress. The purpose of this study was to determine the relationship between workload and employee stress levels in PT. Rev. Pradana Binamulia. Methods: This research is non-experimental with quantitative methods, the type used is cross sectional with analytical observational research design. The population used is employees who work in PT. Wahyu PradanaBinamulia as many as 600 people with the number of samples taken as many as 170 respondents. The research instruments used were questionnaires from O'Donnell and Eggemeier to measure workload, and a DASS (Depression Anxiety Stress Scale) questionnaire to measure stress levels. Results: Data analysis using the chi-square test and obtained results of p <0.01 with a meaningfulness level of 5% (α=0.05) means that there is a significant relationship between workload and stress levels of PT employees. Wahyu PradanaBinamulia Conclusion: Most employees face heavy workload besides the stress level experienced by the majority of employees heavy stress.